Analisis Kinerja Simpang Tak Bersinyal Masjid Al Akbar Kabupaten Balangan - Nova Widayanti (Lambung Mangkurat University Press, 2023)
An intersection is an area where two or more roads join or intersect. At the intersection, there is a conflict between currents from opposite directions, and they cut each other, resulting in congestion along the intersection arm. The existence of a conflict at the intersection will result in disruption to the movement of vehicles which causes delays and long queues of vehicles. The road section at the intersection of the four arms of Al Akbar Mosque Balangan Regency is one of the points that experienced the conflict. Seeing the conflicts that occur at the four-arm intersection, it is necessary to carry out a traffic performance analysis to determine the ability of the road sections to serve the needs of traffic flow. This study aims to analyze the performance of unsignalized four-arm intersections based on the Indonesian Road Capacity Manual (MKJI) 1997 and analyze intersections to improve the performance of the unsignalized four-arm intersections. The method used in this study was primary data collection by conducting field surveys, namely research conducted directly in the field, to obtain the required data. The study results show the most significant traffic flow level when the existing conditions occur at 16.30-17.30 WITA. From the analysis performed, it was obtained that the degree of saturation (DS) was 0.260 <0.75, the average traffic delay was 7.12 sec/pcu <10 sec/pcu, and the Queue Opportunity value (QP) was 7. 82% <35%, The average delay of the intersection is 2.56 sec/pcu. From the parameters, the performance of the intersection shows the level of service